2022
DOI: 10.3390/rs14020375
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation of GOSAT Methane in the Hemispheric CMAQ; Part II: Results Using Optimal Error Statistics

Abstract: We applied the parametric variance Kalman filter (PvKF) data assimilation designed in Part I of this two-part paper to GOSAT methane observations with the hemispheric version of CMAQ to obtain the methane field (i.e., optimized analysis) with its error variance. Although the Kalman filter computes error covariances, the optimality depends on how these covariances reflect the true error statistics. To achieve more accurate representation, we optimize the global variance parameters, including correlation length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…Since cross-validation is a promising technique for maintaining that goal, this research extends cross-validation application to GOSAT satellite observations and multiple covariance parameters estimation. The details of the assumptions and the modifications, along with 48 the evaluation of the assimilation analysis against independent sources of observations, are demonstrated in Chapter 6 (Voshtani et al 2022b).…”
Section: Potential Use Of Parametric Filtering For Methane Assimilationmentioning
confidence: 99%
See 4 more Smart Citations
“…Since cross-validation is a promising technique for maintaining that goal, this research extends cross-validation application to GOSAT satellite observations and multiple covariance parameters estimation. The details of the assumptions and the modifications, along with 48 the evaluation of the assimilation analysis against independent sources of observations, are demonstrated in Chapter 6 (Voshtani et al 2022b).…”
Section: Potential Use Of Parametric Filtering For Methane Assimilationmentioning
confidence: 99%
“…This thesis in Chapters 5 and 6 presents the development and results of the PvKF assimilation system using GOSAT methane and the hemispheric CMAQ model (Voshtani et al 2022a(Voshtani et al , 2022b. It is shown that the PvKF algorithm, besides its simplicity, is welladapted for the assimilation of long-lived species without loss of variance.…”
Section: Paramteric Varaince Kalman Filter (Pvkf)mentioning
confidence: 99%
See 3 more Smart Citations